Influence micromechanical and reologcal properties of the thermotreated steel on tribology indexes - Шевеля, В.В.; Трытек, А.C.; Coкoлaн, Ю.C. (Problems of Tribology, 2014)
A question is considered about influence of heat treatment (tempering and vacations) became on tribotechnical parameters taking to account that directly in the conditions of friction material is exposed to dynamic thermomechanical influence. Influence is studied micromechanical and reological properties became on the processes of contact cooperation.